Outcome Indicators for Evaluating Interventions by Advanced Practice Nurses Specialising in Acute Pain: A Scoping Review - Barroso‐Castaño, Patricia; Cabrera‐Jaime, Sandra; Feijoo‐Cid, Maria; Huertas‐Zurriaga, Ariadna; Benito Aracil, Llúcia (Nursing open, 2025)
ABSTRACT Aim To identify outcome indicators to evaluate interventions delivered by advanced practice nurses specialising in acute pain as reported in the scientific literature. Design Scoping review. Data Sources Three databases (PubMed, Scopus and CINAHL) were systematically searched in December 2023 to identify studies published between 1996 and 2023. Review Methods Search results were managed through the Rayyan platform. Two review authors independently performed data selection and extraction, and a third reviewer resolved conflicts. Results The search identified 1263 studies. After screening titles and s, 14 full‐text studies were selected for data extraction and analysis. These studies encompassed a variety of designs, including randomised controlled trials, cohort studies and observational studies. The outcome indicators used to evaluate advanced practice nurses' interventions in acute pain management were examined across three key dimensions: study population and setting, intervention and model of acute pain nurse care and quality‐of‐care assessment. The specific outcome indicators identified included ‘pain score’, ‘side effects’, ‘analgesia prescription’, ‘non‐pharmacological interventions’, ‘nurses' pain management knowledge’, ‘patient/parent education’ and ‘APN contact’. Conclusion This review underscores the growing and evolving role of advanced practice nurses (APNs) in acute pain management, highlighting the diversity of care models and interventions implemented across clinical settings. Key outcome indicators, such as ‘pain score’, ‘side effects’ and ‘nursing staff's understanding of pain management’, were identified, with certain indicators, like ‘APN contact’ and ‘non‐pharmacological interventions’, more closely linked to the nurse‐led approach. Implications for the Profession This scoping review underscores the importance of developing and evaluating outcome indicators to enhance the assessment of interventions provided by advanced practice nurses in acute pain management. While consensus on specific indicators has not yet been reached, this review highlights the need for further research to refine and standardise these indicators, thereby contributing to more uniform and comparative evaluations of care. Impact The identified outcome indicators can inform the evaluation of APN interventions in acute pain management, supporting efforts to optimise and standardise care. Further implementation and assessment of these indicators will be essential to enhance the quality and effectiveness of patient care. Reporting Method The PRISMA extension for Scoping Review guidelines was used. Patient or Public Contribution No patient or public contribution.